International legal experience of personal data protection: ways of improvement for Ukraine - Сопілко, Ірина Миколаївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2014)
The features of protection of the personal data in the practice of the European countries are studied in the article. Moreover, the author determines the main menaces of the modern information space in Ukraine.